Employee Motivation And Learning Behaviours In Selected Manufacturing Industries - Mat, Shafizal (UTeM, 2016)
The topics of motivation and job satisfaction have been of interest to researchers over the past decades. Many researchers and practitioners have studied the driving factors to motivate staff in the workplace, but no specific findings have shown correlation between motivation and job satisfaction. Problems of motivation and job satisfaction have continued to plague many developing countries like Malaysia. This study is an attempt to improve the understanding of the human contribution to variability in manufacturing industries and the focus areas are work motivation, satisfaction and performance as well as relationships with learning behaviours of employees in the workplace. The research work can be categorized into three parts. The first part consists of pilot study which was conducted to determine the practicality and validity of method/instruments used in the research. The pilot study also helped to correct the flaws/weaknesses of the method before employing it in the full-scale research study. Secondly, an experimental study was carried out to identify the motivation, satisfaction, performance and learning behaviour of unskilled and skilled employees doing simple or complex tasks individually or in group. The final part was an industrial study conducted with 356 employees from various positions and backgrounds in selected manufacturing industries in Malaysia. Based on the findings, it has been shown that unskilled employees preferred doing complex tasks in a group rather than doing simple tasks and skilled employees preferred doing complex tasks individually rather than in a group. It increased their work motivation, satisfaction and performance. It was found that task identity (simple tasks) and learning behaviours (individual learning of unskilled employees) can be the reason for employees to leave in the future. The task identity (task complexity) can be an important factor in job design in organisations and it is significant in the learning process of unskilled and skilled employees in manufacturing industries, particularly in Malaysia. It was also found that learning in a team (group) appears to be a very significant factor in workplace learning for both unskilled and skilled employees. The study has shown that there are relationships between motivational and learning behaviours of skilled and unskilled employees and this knowledge is expected to be useful for employers and policy makers in organisations especially in manufacturing industries in Malaysia.